1993
DOI: 10.1046/j.1537-2995.1993.331194082383.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of modified crosslinked cell‐free hemoglobin for human use: the role of quantitative determination of endotoxin contamination

Abstract: In vivo toxicity remains a major barrier to the successful use of cell-free hemoglobin (Hb) as an oxygen carrier in humans. Bacterial endotoxin (lipopolysaccharide, LPS) is known to contribute to the in vivo toxicity of Hb preparations, and the prevention of LPS contamination is a critical aspect of the effort to create an efficacious Hb blood substitute. Limulus amebocyte lysate assays for endotoxin were performed on multiple Hb samples from 26 independent production runs for the preparation of human crosslin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…In previous publications, considerable increases of the biological activities of LPS in the LAL test (8,11,12,35), production of mononuclear cell tissue factor (35), and stimulation of endothelial cell tissue factor production (36, 37) as a result of Hb binding to LPS were described. Furthermore, an increase of endotoxin binding to endothelial cells and increased lethal toxicity were reported (13,36).…”
Section: Discussionmentioning
confidence: 94%
“…In previous publications, considerable increases of the biological activities of LPS in the LAL test (8,11,12,35), production of mononuclear cell tissue factor (35), and stimulation of endothelial cell tissue factor production (36, 37) as a result of Hb binding to LPS were described. Furthermore, an increase of endotoxin binding to endothelial cells and increased lethal toxicity were reported (13,36).…”
Section: Discussionmentioning
confidence: 94%
“…Bacterial LPS is an amphiphilic gigantic macromolecule, therefore, it hydrophobically interacts with protein and biomembranes 20. Hb strongly interacts with LPS, showing synergistic toxicity 21–23. The constituent of endotoxin that causes LAL gelation is a glycophospholipid that is designated lipid‐A 24.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has demonstrated that Hb forms stable complexes with a wide variety of LPSs and that LPS macromolecular particles become disaggregated after binding to Hb (11,12). In a series of in vitro studies, Hb was shown to enhance the ability of LPS to activate coagulation (11,25), stimulate procoagulant activity from peripheral blood mononuclear cells (25), and stimulate production of procoagulant activity by cultured human endothelial cells (23). LPS binding to endothelial cells was increased when LPS was complexed with Hb (24), suggesting a possible mechanism for the enhanced cellular response to LPS-Hb complexes compared to LPS alone.…”
mentioning
confidence: 99%